Land use patterns and climate change: a modeled scenario of the Late Bronze Age in Southern Greece : letter - Knitter, Daniel; Günther, Gerrit; Hamer, Wolfgang Berengar; Keßler, Torben; Seguin, Joana; Unkel, Ingmar; Weiberg, Erika; Duttmann, Rainer; Nakoinz, Oliver (Environmental research letters, 2019)
In this study, we present a modeling approach that investigates how much cultivable land was required to supply a society and whether societies were in need when environmental conditions deteriorated. The approach is implemented for the North-Eastern Peloponnese and is based upon the location of Late Helladic IIIB (1300-1200 BCE) archaeological sites, an assessment of their sizes, and a proposed diet of the people. Based on these information, the areal requirement of each site is calculated and mapped. The results show that large sites do not have sufficient space in their surroundings in order to supply themselves with the required food resources and thus they depended on supplies from the hinterland. Dry climatic conditions aggravate the situation. This indicates that potential societal crisis are less a factor of changing environmental conditions or a shortage of arable land but primarily caused by socio-economic factors.